Determinant factors for building the soybean yield potential in southern Brazil - Bredow, Alex Alan (2020)
The soybean is an alternative of diversification and financial return to the rice farmer. However, it presents difficulties of cultivation and low yield due to the physical characteristics of the soil. In this scenario, the objective of this work was to verify the influence of soil scarification, the genetic material used and the sowing date. Three soybean cultivars, with yield potential classified as “medium”, “high” and “very high”, were sown in a scarified and non-scarified area, in the dates november 7th and december 10th, year of 2018. The scarification opperation occurred on october 1st. Initial establishment varied according to cultivar, soil mechanism and sowing date. Soil scarification effect was verified up to 100 days after the operation. Within the construction of the yield potential, scarification accounted for 14.4 %, sowing date 12.5 % and genetic material 73.1 % of crop grain yield, in the “high” and “very high” potential materials.